Cultural and Communication Approaches in the Design of Visual Communication Design Works - Sigied Himawan Yudhanto; Faizal Risdianto; Aphief Tri Artanto (Journal of linguistics, culture and communication, 2023)
This paper discusses culture and communication, which are essential in designing visual communication design works (visual communication design). A student and professional designer with a good understanding of culture and communication can create appropriate and effective designs for the target audience. Designers need to study the target audience's values, norms, Language, and beliefs. This is conducted to ensure the designs are acceptable to the target audience in achieving the desired goals. Designers must also consider visual elements such as colors, typography, symbols, and images appropriate to the target audience's culture. The designer must have a right and measurable design concept to accommodate cultural values and norms that are adapted to the placement conditions and the target market of the users of the visual communication design product. In the test and evaluation stage, the designer must test the design on an audience that fits the consumer culture. After that, the designer needs to evaluate the audience's response to the visual communication design product that is produced, including the effectiveness and readability of the message conveyed through the design communication. In conclusion, understanding culture and communication is crucial in designing visual communication designs. Designers who consider these factors can create appropriate and effective designs and solve design problems.